Recycling method of waste ternary lithium batteries

By performing multi-step processing on waste ternary lithium batteries, NiMn2O4 or CoMn2O4 spinel materials are prepared, which solves the technical problems of heavy metal recovery and spinel catalyst preparation in waste lithium batteries, and achieves efficient catalytic degradation effects.

CN118702163BActive Publication Date: 2025-04-22JIANGSU UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410824894.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-04-22
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recycle heavy metal elements in waste ternary lithium batteries, and no reports have been seen in preparing spinel catalysts from waste ternary lithium batteries.

Method used

By discharging, dismantling, removing aluminum from the positive electrode sheet and pyrolyzing the waste ternary lithium battery, the positive electrode powder is obtained, and NiMn2O4 or CoMn2O4 spinel material is prepared through acid leaching, decomposition, extraction and precipitation steps.

Benefits of technology

Effective recycling and utilization of cobalt, nickel and manganese elements in waste batteries were achieved to prepare manganese-based spinel materials with good catalytic properties, which can synergistically degrade VOCs and NOx with plasma.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004910192980000011
    Figure HDA0004910192980000011
  • Figure HDA0004910192980000021
    Figure HDA0004910192980000021
  • Figure HDA0004910192980000031
    Figure HDA0004910192980000031
Patent Text Reader

Abstract

The invention discloses a method for recycling waste ternary lithium batteries, which recycles and utilizes cobalt, nickel and manganese elements in waste batteries to synthesize manganese-based spinel NiMn2O4 or CoMn2O4, which can be used as a catalyst to synergistically catalyze the degradation of VOCs and NOx with plasma. Both recycled and prepared materials show very good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waste battery recycling, and in particular to a method for recycling waste ternary lithium batteries. Background Art

[0002] Ternary lithium battery materials have many advantages, such as large capacity, good cycle performance and thermal stability, and are therefore considered one of the most promising new lithium-ion battery cathode materials. The recycling of waste ternary lithium batteries is crucial to environmental protection, and the heavy metal elements contained in them also have high recycling value.

[0003] At present, the main recycling methods for ternary lithium battery materials include dry, wet and biological methods. Dry recycling processes waste batteries through physical crushing and high-temperature calcination, but the calcination process will reduce the charge and discharge performance of the material. Wet recycling uses acid leaching, but high-concentration acid leaching may cause corrosion to equipment and the environment. The biological method uses microorganisms to separate valuable metal elements from solids, but there are problems such as difficulty in cultivating strains and separation of leachates. How to efficiently recycle heavy metal elements in waste ternary lithium batteries is an urgent technical problem.

[0004] Regarding wet recycling methods, the purpose of many recycling processes is to regenerate and recover the positive electrode material, including direct regeneration and indirect regeneration.

[0005] Direct regeneration For example, Chinese patent document CN112563604A discloses a method for regenerating waste lithium-ion battery positive electrode materials. The invention achieves full and uniform lithium replenishment of waste positive electrode materials by electrolysis, and then combines heat treatment to restore the material structure. Direct regeneration usually can only restore performance to a general level.

[0006] Indirect regeneration, for example, Chinese patent document CN 115637328 A (202211365941.6) discloses a method for recycling waste zinc-carbon and lithium-ion batteries to prepare LiMn2O4, comprising the following steps: using leaching precipitation method to recover different waste batteries to obtain Mn2O3 and Li2CO3, and mixing the two in a certain proportion by solid-state synthesis method under certain temperature and conditions to generate LiMn2O4 positive electrode material. The indirect regeneration process is relatively long.

[0007] Some recycling technologies aim to separate and recover valuable metals from batteries.

[0008] For example, Chinese patent document CN113957255B (application number 202111159214.X) discloses a method for separating and recovering valuable metals in waste ternary lithium batteries: oxidative acid leaching of waste ternary lithium battery powder; adding alkali solution to the leachate for precipitation reaction, then adding sulfide salt for reaction, adjusting the pH, and precipitation reaction to obtain nickel hydroxide precipitate and liquid phase A; adding carbonate to liquid phase A for reaction, solid-liquid separation, and obtaining lithium carbonate; calcining the leached residue, adding chlorate for co-heating, solid-liquid separation, and obtaining manganese dioxide.

[0009] So far, there are no reports on the preparation of spinel catalysts from recycled components of waste ternary lithium batteries. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a method for recycling waste ternary lithium batteries. By using this method, a manganese-based spinel catalyst can be obtained, which can be used as a catalyst to synergistically catalyze the degradation of VOCs and NOx with plasma.

[0011] The technical solution for achieving the first object of the present invention is a method for recycling waste ternary lithium batteries to obtain NiMn2O4 spinel material, comprising the following steps:

[0012] ①Discharge and disassemble the waste ternary lithium batteries, remove aluminum from the positive electrode sheets, and pyrolyze the positive electrode sheets to obtain positive electrode powder.

[0013] ② Acid leaching and impurity removal;

[0014] The positive electrode powder obtained in step ① is subjected to acid leaching using sulfuric acid and hydrogen peroxide to obtain a leachate;

[0015] Add di(2-ethylhexyl)phosphoric acid extractant to the leachate, shake and mix well, pour into a separatory funnel, let stand and take out the water layer; add trioctyldecyl tertiary amine extractant to the separated water layer, and obtain a mixed solution containing only Ni and Mn after separation, and detect the element concentrations of Ni and Mn in the mixed solution.

[0016] ③ According to the measured element concentrations of Ni and Mn, manganese salt is added to the mixed solution after calculation, ethanol is added and stirred evenly, and then oxalic acid solution is added to the mixed solution. The obtained precipitate is centrifuged, washed, dried, and calcined to obtain NiMn2O4 spinel material.

[0017] In the above step ①, when removing aluminum from the positive electrode sheet, the positive electrode sheet is cut into small pieces and placed in an excess of sodium hydroxide solution to react and remove aluminum.

[0018] In the above step ①, when the positive electrode sheet is pyrolyzed, the positive electrode sheet of the battery after aluminum removal is pyrolyzed at a high temperature of 600±20° C. for 4 to 6 hours to remove acetylene black and polyvinylidene fluoride.

[0019] In the above step ②, when di(2-ethylhexyl)phosphoric acid is added for extraction, the extraction phase ratio O / A = 2 / 1; when trioctyldecyl tertiary amine is added for extraction, the extraction phase ratio can be adjusted.

[0020] In the above step ③, the supplemented manganese salt is selected from manganese salts such as manganese acetate and manganese nitrate. Preferably, the molar ratio of Ni to Mn after supplementation is 1:2; the precipitation is calcined in air at 400±20°C for 2.5 to 4 h to obtain NiMn2O4 spinel material.

[0021] The technical solution for achieving the second object of the present invention is a method for recycling waste ternary lithium batteries to obtain CoMn2O4 spinel material, comprising the following steps:

[0022] ①Discharge and disassemble the waste ternary lithium batteries, remove aluminum from the positive electrode sheets, and pyrolyze the positive electrode sheets to obtain positive electrode powder.

[0023] ② Acid leaching and impurity removal;

[0024] The positive electrode powder obtained in step ① is subjected to acid leaching using sulfuric acid and hydrogen peroxide to obtain a leachate;

[0025] Add di(2-ethylhexyl)phosphoric acid to the leachate, shake and mix, pour into a separatory funnel, let stand and take out the water layer; add dimethylglyoxime to the separated aqueous solution, stir until precipitation is complete, filter the precipitate to obtain a clear aqueous solution, and detect the element concentrations of Co and Mn in the mixed solution.

[0026] ③ According to the measured element concentrations of Co and Mn, Co salt or Mn salt is added to the mixed solution after calculation, ethanol is added and stirred evenly, and then oxalic acid solution is added to the mixed solution. The obtained precipitate is centrifuged, washed, dried, and calcined to obtain CoMn2O4 spinel material.

[0027] In the above step ①, when removing aluminum from the positive electrode sheet, the positive electrode sheet is cut into small pieces and placed in an excess of sodium hydroxide solution to react and remove aluminum; when pyrolyzing the positive electrode sheet, the battery positive electrode sheet after aluminum removal is pyrolyzed at a high temperature of 600±20°C for 4 to 6 hours to remove acetylene black and polyvinylidene fluoride.

[0028] In the above step ②, when di(2-ethylhexyl)phosphoric acid is added for extraction, the extraction phase ratio O / A can be adjusted; when dimethylglyoxime is added, the extraction phase ratio O / A can be adjusted, and after adding dimethylglyoxime, stirring is performed at 60±5° C. until precipitation is complete.

[0029] In the above step ③, the supplemented Co salt is selected from cobalt salts such as cobalt acetate and cobalt nitrate, and the supplemented Mn salt is selected from manganese salts such as manganese acetate and manganese nitrate; preferably, the molar ratio of Co to Mn after supplementation is 1:2; the precipitation is calcined in air at 400±20℃ for 2.5 to 4 h to obtain CoMn2O4 spinel material.

[0030] The technical solution for achieving the third object of the present invention is to use the NiMn2O4 and CoMn2O4 spinel materials prepared according to the above method as catalysts to synergistically catalyze the degradation of VOCs and NOx with plasma energy.

[0031] The present invention has positive effects:

[0032] (1) The present invention effectively recycles and utilizes cobalt, nickel and manganese elements in waste batteries to synthesize manganese-based spinel NiMn2O4 or CoMn2O4, which can be used as a catalyst to synergistically catalyze the degradation of VOCs and NOx with plasma.

[0033] (2) Both NiMn2O4 and CoMn2O4 spinel materials recovered by the present invention present a typical uniform particle structure.

[0034] The prepared NiMn2O4 particles have a size less than 2 μm, a regular and uniform particle shape, and a rich porous structure on the surface, which is conducive to the diffusion of gas into the interior of NiMn2O4 for reaction. EDS analysis reveals that Ni, Mn and O elements are evenly distributed in the catalyst.

[0035] The nanoflower morphology of the prepared CoMn2O4 was basically observed, with a compact structure and good organization, which is very conducive to the surface reaction. The two materials can synergistically catalyze the degradation of VOCs and NOx with plasma energy.

[0036] Both materials showed very good catalytic performance.

[0037] (3) The preparation of spinel materials usually requires high-purity raw materials, while the metals extracted from waste lithium batteries can reach the required purity requirements after proper treatment and impurity removal. Therefore, the recycling method of the present invention has a higher economic added value. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is the XRD pattern; Figure 1 (a) is the XRD pattern of NiMn2O4 prepared in Example 1, Figure 1 (b) is the XRD pattern of CoMn2O4 prepared in Example 2.

[0039] Figure 2 For SEM photos and element distribution diagrams; Figure 2 (a) is a SEM photo and element distribution diagram of NiMn2O4 prepared in Example 1, wherein Figure 2 (b) is the SEM photograph and element distribution map of CoMn2O4 prepared in Example 2.

[0040] Figure 3This is a comparison chart of toluene degradation effects under DBD degradation alone, DBD+NiMn2O4, and DBD+CoMn2O4 synergistic catalysis in Experimental Example 1.

[0041] Figure 4 This is a comparison chart of energy efficiency under DBD degradation alone, DBD+NiMn2O4, and DBD+CoMn2O4 synergistic catalysis in Experimental Example 1.

[0042] Figure 5 This is a comparison chart of the byproduct O3 generation under DBD degradation alone, DBD+NiMn2O4, and DBD+CoMn2O4 synergistic catalysis in Experimental Example 1.

[0043] Figure 6 This is a comparison chart of the byproduct NO2 generation under DBD degradation alone, DBD+NiMn2O4, and DBD+CoMn2O4 synergistic catalysis in Experimental Example 1. DETAILED DESCRIPTION

[0044] (Example 1)

[0045] This embodiment recycles waste ternary lithium batteries to prepare NiMn2O4 manganese-based spinel materials. Battery positive electrode materials generally include metals such as nickel, cobalt, manganese, lithium, aluminum, iron, and copper. This embodiment removes impurities from other metals and uses nickel and manganese to prepare NiMn2O4, specifically including the following steps:

[0046] ① Obtain positive electrode powder.

[0047] Discharge the used lithium battery in 5% NaCl solution for 24 to 48 hours; after discharge, take out the battery, clean it with distilled water and dry it, and measure the voltage ≤0.5V for manual disassembly; after disassembly, obtain the positive and negative electrode materials, shell, and plastic film of the used ternary lithium battery respectively. The above disassembly work is carried out in a fume hood, and protective gloves and masks are worn.

[0048] The positive electrode material was naturally dried in a fume hood. After drying, the positive electrode sheet was cut into small pieces of about 20 mm × 20 mm, placed in an excess of 40 g / L sodium hydroxide solution, and reacted at 50 ° C for 60 minutes to remove aluminum (solid-liquid ratio 10 g / L).

[0049] 2 g of the battery positive electrode sheet after aluminum removal was taken out, and pyrolyzed at a high temperature of 600±20° C. (600° C. in this embodiment) for 4 to 6 h (5 h in this embodiment) to remove acetylene black and polyvinylidene fluoride (PVDF). After cooling, the positive electrode powder was taken out and fully ground.

[0050] ② Acid leaching and impurity removal.

[0051] The positive electrode powder obtained in step ① was added into a conical flask, and sulfuric acid and hydrogen peroxide were added into the flask. The liquid-to-solid ratio in the conical flask was 25 mL / g, the sulfuric acid concentration was 2.5 mol / L, and the amount of hydrogen peroxide added was 5 vol.%. The mixture was reacted at 80 °C for 80 min to obtain a leachate.

[0052] D2EHPA (di(2-ethylhexyl)phosphoric acid) was added to the leachate at a ratio of extract phase O / A = 1 / 1 to 5 / 1 (2 / 1 in this embodiment) to remove impure metals. The mixture was shaken and mixed for 5 minutes and then poured into a separatory funnel. The aqueous layer was taken out after standing for 20 minutes.

[0053] Subsequently, N-235 (trioctyldecyl tertiary amine) extractant with a volume ratio of 20% using PEG-20000 as solvent was added to the aqueous layer obtained above at an extraction phase ratio of O / A = 1 / 1 to 5 / 1 (2 / 1 in this embodiment) to remove cobalt. After continuous shaking for 30 minutes, the mixture was poured into a separatory funnel and allowed to stand for 60 minutes before the aqueous layer was taken out. The metal content in the aqueous layer was measured by an atomic absorption spectrometer. The Ni element concentration in the obtained mixed solution was 300.8 mg / L, and the Mn element concentration was 149.24 mg / L.

[0054] ③ Take 827.26 mL of the above aqueous layer mixed solution, weigh 1.0750 g of manganese acetate and add it to the solution, add 4.23 mL of 95% ethanol and stir evenly at 80 ° C; add 42.3 mL of 0.24 mol / L oxalic acid solution to the above mixed solution and stir at 80 ° C for 0.5 h; centrifuge the reacted material at 7000 rpm, wash the obtained precipitate three times with deionized water and then wash it once with alcohol, then dry the precipitate at 80 ° C for 12 h, then increase the temperature from room temperature to 400 ° C at a heating rate of 5 ° C / min, and calcine in air for 3 h to obtain NiMn2O4 spinel material, which is ground for standby use.

[0055] In addition to manganese acetate, manganese nitrate can also be used to supplement manganese.

[0056] The obtained material was analyzed by XRD. Figure 1 (a), six characteristic diffraction peaks appear at 18.2°, 30.0°, 36.7°, 42.6°, 56.6°, and 62.4°, corresponding to standard card #01-1110 (NiMn2O4), indicating that NiMn2O4 was successfully synthesized in this example.

[0057] The SEM photo and element distribution diagram of NiMn2O4 prepared in this embodiment are shown in Figure 2(a) As can be seen from the figure, NiMn2O4 presents a typical uniform particle structure. The prepared NiMn2O4 particle size is less than 2 μm, the particle shape is regular and uniform, and the surface has a rich pore structure, which is conducive to the diffusion of gas into the interior of NiMn2O4 for reaction; EDS analysis reveals that Ni, Mn and O elements are uniformly distributed in the catalyst.

[0058] (Example 2)

[0059] This embodiment recycles waste ternary lithium batteries to prepare CoMn2O4 manganese-based spinel materials, including the following steps:

[0060] ① Obtain positive electrode powder.

[0061] Discharge the used lithium battery in 5% NaCl solution for 24 to 48 hours; after discharge, take out the battery, clean it with distilled water and dry it, and measure the voltage ≤0.5V for manual disassembly; after disassembly, obtain the positive and negative electrode materials, shell, and plastic film of the used ternary lithium battery respectively. The above disassembly work is carried out in a fume hood, and protective gloves and masks are worn.

[0062] The positive electrode material was naturally dried in a fume hood. After drying, the positive electrode sheet was cut into small pieces of about 20 mm × 20 mm, placed in an excess of 40 g / L sodium hydroxide solution, and reacted at 50 ° C for 60 minutes to remove aluminum (solid-liquid ratio 10 g / L).

[0063] 2 g of the battery positive electrode sheet after aluminum removal was taken out, and pyrolyzed at 600° C. for 5 h to remove acetylene black and polyvinylidene fluoride (PVDF). After cooling, the positive electrode sheet was taken out and fully ground to obtain positive electrode powder.

[0064] ② Acid leaching and impurity removal.

[0065] The positive electrode powder obtained in step ① was added into a conical flask, and sulfuric acid and hydrogen peroxide were added into the flask. The liquid-to-solid ratio in the conical flask was 25 mL / g, the sulfuric acid concentration was 2.5 mol / L, and the amount of hydrogen peroxide added was 5 vol.%. The mixture was reacted at 80 °C for 80 min to obtain a leachate.

[0066] Add D2EHPA (di(2-ethylhexyl)phosphoric acid) to the leachate at a ratio of O / A = 2 / 1 to remove impure metals. After oscillating and mixing for 5 minutes, pour into a separatory funnel and take out the water layer after standing for 20 minutes. The D2EHPA extraction ratio is adjustable, and the amount added should ensure that the impure metals are completely removed.

[0067] Add DMG (dimethylglyoxime) to the separated aqueous solution, stir at 60°C for 30 minutes until the precipitation is complete, filter the precipitate to obtain a clear aqueous solution; the dimethylglyoxime extraction ratio is adjustable, and the amount added should ensure that Ni is completely removed. The concentration of Co in the obtained mixed solution is 58.08 mg / L, and the concentration of Mn is 165.60 mg / L, which are set aside.

[0068] ③ Take 2.9589 L of the above mixed solution, weigh 0.2732 g of cobalt acetate and add it to the solution, add 4.459 mL of 95% ethanol and stir at 80 ° C; add 44.59 mL of 0.24 mol / L oxalic acid solution to the above mixed solution, stir at 80 ° C for 0.5 h, centrifuge the reacted material at 7000 rpm, wash the obtained precipitate three times with deionized water and then wash it once with alcohol, then dry the precipitate at 80 ° C for 12 h, then increase the temperature from room temperature to 400 ° C at a heating rate of 5 ° C / min, and calcine in air for 3 h to obtain CoMn2O4 spinel material, which is ground for standby use.

[0069] In this step, the amount of the element in the solution after impurity removal determines whether to add Co salt or Mn salt. If there is more Co and less manganese, Mn salt is added, and if there is less Co and more manganese, Co salt is added. The added Co salt is selected from Co salts such as cobalt acetate and cobalt nitrate, and the added Mn salt is selected from Mn salts such as manganese nitrate and manganese carbonate. In this embodiment, Co salt is added.

[0070] The obtained material was analyzed by XRD. Figure 1 (b), there are 7 characteristic diffraction peaks at 19.2°, 28.9°, 32.5°, 38.8°, 45.5°, 59.2°, and 61.3°, corresponding to standard card #01-1126 (CoMn2O4), indicating that CoMn2O4 was successfully synthesized in this example.

[0071] The SEM photo and element distribution diagram of CoMn2O4 prepared in this example are shown in Figure 2 (b) It can be seen from the figure that CoMn2O4 presents a typical uniform particle structure, and the morphology is nanoflower-shaped, with a compact structure and good organization, which is very conducive to the surface reaction; at the same time, chemical analysis performed by EDS reveals the composition signals of Co, Mn, and O.

[0072] (Test Example 1)

[0073] This test example compares the degradation rates of VOCs and nitrogen oxides by dielectric barrier discharge (DBD) low temperature plasma coupled with NiMn2O4 synergistic catalytic degradation, dielectric barrier discharge (DBD) low temperature plasma coupled with CoMn2O4 synergistic catalytic degradation, and dielectric barrier discharge (DBD) low temperature plasma degradation. The test process is as follows:

[0074] The gas configuration is as follows: the nitrogen from the compressed cylinder is controlled by a mass flow controller (MFC) at a certain flow rate, and then passes through a polytetrafluoroethylene tube with an outer diameter of 3 mm as a carrier gas or balance gas and enters a stainless steel tank containing liquid VOCs (the stainless steel tank is temperature-controlled by a low-temperature water tank or a water bath), carrying out VOCs vapor, and is fully mixed with the other two nitrogen and oxygen controlled by mass flow meters in the mixer to form a stable concentration of VOCs gas. Another nitrogen oxide is connected to the mixing tank and the above-mentioned stable concentration of VOCs gas enters the DBD discharge reactor together for a plasma catalytic VOCs degradation experiment.

[0075] The experimental conditions are as follows: O2 concentration 4%, toluene initial concentration 300 mg / m 3 The initial NO concentration was 200 mg / m 3, The gas flow rate was 1L / min, and the plasma energy density was adjusted to 162.65 J / L, 298.87 J / L, 421.24 J / L, 563.10 J / L and 766.35 J / L. The degradation effects of toluene and NO by DBD, DBD+NiMn2O4 or DBD+ CoMn2O4 at different powers were compared.

[0076] The experimental results are statistically shown later. Figures 3 to 6 .

[0077] Depend on Figure 3 It can be seen that the DBD catalytic system has a higher toluene removal efficiency than the single DBD system. When the SED increases from 162.65 J / L to 766.35 J / L, the degradation efficiency of the single DBD system increases from 19.27% ​​to 83.88%. For DBD+NiMn2O4 and DBD+CoMn2O4, when the SED increases from 162.65 J / L to 766.35 J / L, the toluene removal rate increases from 46.32% and 47.40% to 89.85% and 93.00%, respectively; in addition, at the same SED value, the CoMn2O4 catalyst exhibits better catalytic performance. In addition, all NO is converted into NO2 and N2O and other intermediates, and the removal efficiency is 100%.

[0078] Depend on Figure 4It can be seen that with the increase of energy density, the energy efficiency shows a decreasing trend. Under the same SED, the energy efficiency of the DBD catalytic system is significantly higher than that of DBD degradation alone. When the SED is 162.65 J / L, the energy efficiency value of the DBD system alone is 6.00 g·kWh. -1 , while the energy efficiency values ​​of DBD+NiMn2O4 and DBD+CoMn2O4 are 10.70 g·kWh, respectively. -1 and 10.95 g·kWh -1 .

[0079] Depend on Figure 5 It can be seen that the O3 concentration decreases with the increase of SED. When the SED is 766.35 J / L, the O3 concentration in the DBD system alone is about 104.72 mg·m -3 , while for DBD+NiMn2O4 and DBD+CoMn2O4, the O3 concentration dropped to 61.94 mg·m -3 and 1.05 mg·m -3 From low to high energy density, the O3 produced by CoMn2O4 catalyst in DBD catalysis process is always much lower than that of NiMn2O4 catalyst.

[0080] Depend on Figure 6 It can be seen that with the increase of energy density, the concentration of NO2 generated shows a trend of gradual increase. Compared with the single DBD system, the concentration of NO2 generated in the DBD catalytic system is significantly increased, among which the NO2 generation amount of CoMn2O4 catalyst is higher than that of NiMn2O4 catalyst.

Claims

1. A method for recycling waste ternary lithium batteries, characterized in that The following steps are involved: ①Discharge and disassemble the waste ternary lithium batteries, remove aluminum from the positive electrode sheets, and pyrolyze the positive electrode sheets to obtain positive electrode powder; ② Acid leaching and impurity removal; The positive electrode powder obtained in step ① is subjected to acid leaching using sulfuric acid and hydrogen peroxide to obtain a leachate; Add di(2-ethylhexyl)phosphoric acid extractant to the leaching solution, shake and mix well, pour into a separatory funnel, and take out the water layer after standing; add 20% by volume trioctyldecyl tertiary amine extractant with PEG-20000 as solvent to the separated water layer, and obtain a mixed solution containing only Ni and Mn after separation, and detect the element concentrations of Ni and Mn in the mixed solution; ③ According to the measured element concentrations of Ni and Mn, manganese salt is added to the mixed solution after calculation, ethanol is added and stirred evenly, and then oxalic acid solution is added to the mixed solution. The obtained precipitate is centrifuged, washed, dried, and calcined to obtain NiMn2O4 spinel material.

2. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In step ①, when removing aluminum from the positive electrode sheet, the positive electrode sheet is cut into small pieces and placed in an excess of sodium hydroxide solution to react and remove aluminum.

3. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In step ①, when the positive electrode sheet is pyrolyzed, the battery positive electrode sheet after aluminum removal is pyrolyzed at a high temperature of 600±20°C for 4 to 6 hours to remove acetylene black and polyvinylidene fluoride.

4. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In step ②, when di(2-ethylhexyl)phosphoric acid is added for extraction, the extraction phase ratio O / A is 1 / 1 to 5 / 1; when trioctyldecyl tertiary amine is added for extraction, the extraction phase ratio O / A is 1 / 1 to 5 / 1.

5. The method for recycling waste ternary lithium batteries according to claim 1, characterized in that: In step ③, the supplemented manganese salt is manganese acetate and / or manganese nitrate; the precipitate is calcined in air at 400±20°C for 2.5 to 4 h to obtain NiMn2O4 spinel material.

Citation Information

Patent Citations

  • Regeneration method of waste lithium ion battery positive pole material

    CN112563604A

  • A method for separating and recycling valuable metals from waste ternary lithium batteries

    CN113957255B

  • Method for preparing nickel and cobalt doped lithium manganate by using waste and old lithium ionic cell as raw material

    CN101450815A

  • Nanoflower spinel CoMn2O4 catalyst for catalytic oxidation of VOCs (Volatile Organic Compounds), preparation method and application

    CN108295866A

  • Method for preparing spinel type catalyst for catalytic combustion of VOCs under assistance of low-temperature plasma

    CN111905714A